2011
DOI: 10.1007/s12011-011-9235-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Selenium and Cancer Cell Xenograft on Peripheral T and B Lymphocytes in Adult Nude Mice

Abstract: Selenium (Se) is known to regulate tumorigenesis and immunity at the nutritional and supranutritional levels. Because the immune system provides critical defenses against cancer and the athymic, immune-deficient NU/J nude mice are known to gradually develop CD8(+) and CD4(+) T cells, we investigated whether B and T cell maturation could be modulated by dietary Se and by tumorigenesis in nude mice. Fifteen homozygous nude mice were fed a Se-deficient, Torula yeast basal diet alone (Se-) or supplemented with 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, extrathymic maturation (spleen, lymph node, and bone marrow) of T cells (NK cells) could be possible when these mice have been burdened with virus or tumor, as reported by several other investigators. 44, 45 Cheng et al 46 also report that selenium increased peripheral and spleen CD4 + and CD8 + cells in the nude mice bearing prostate cancer cells. Moreover, it is noteworthy that postnatal thymic-independent T cell differentiation (maturation) in the extrathymic origin (such as in skin) could be possible.…”
Section: Discussionmentioning
confidence: 93%
“…However, extrathymic maturation (spleen, lymph node, and bone marrow) of T cells (NK cells) could be possible when these mice have been burdened with virus or tumor, as reported by several other investigators. 44, 45 Cheng et al 46 also report that selenium increased peripheral and spleen CD4 + and CD8 + cells in the nude mice bearing prostate cancer cells. Moreover, it is noteworthy that postnatal thymic-independent T cell differentiation (maturation) in the extrathymic origin (such as in skin) could be possible.…”
Section: Discussionmentioning
confidence: 93%
“…Several reports have suggested that Se levels might regulate the function of B cells. Mice fed Se-deficient (0 mg/kg) or Se-high (1.0 mg/kg) diets showed decreased numbers of peripheral B cells (Cheng et al 2012). Similar trends were seen in SeMet-treated mice where mice on low (0.02 ppm) and above-adequate (2 ppm) diets had reduced B cell numbers in the spleen (Vega et al 2007).…”
Section: T Cells and B Cells-mounting Evidence Has Shown That In Vivo Se Levels Maymentioning
confidence: 57%
“…T cells from mice fed high Se diet (1.0 mg/kg) had a much higher proliferation rate than those from Se low (0.08 mg/kg) and medium (0.25 mg/kg) diets (Hoffmann FW et al 2010). An in vivo study using athymic, immune-deficient NU/J nude mice showed that CD4 + T cells were increased in Se-sufficient mice (1.0 mg/kg) compared to mice on Se-deficient (0 mg/kg) or Se-adequate (0.15 mg/kg) diets (Cheng et al 2012). Furthermore, higher Se levels increased free thiols in activated CD4 + T cells, which likely played an important role in the clonal expansion of these cells by favoring the TCR-induced oxidative burst in cells (Hoffmann FW et al 2010).…”
Section: T Cells and B Cells-mounting Evidence Has Shown That In Vivo Se Levels Maymentioning
confidence: 99%
“…Interestingly, we also found that compared to high-dose CN133 (5 mg/kg), CN133 with low dose (1 mg/kg) conferred to a marked reduction in tumors volume in xenograft prostate cancer model of nude mice in our previous study [ 38 ]. Although nude mice are useful model to assess tumor xenograft development because of athymic congenitally, extrathymic T cells including CD4 + or CD8 + cells could partially develop maturation as age growth in nude mice [ 41 , 42 ]. Therefore, data from this time and our previous results demonstrated that low-dose CN133 may efficaciously suppress prostate cancer growth by augment of immunogenicity.…”
Section: Discussionmentioning
confidence: 99%